What stays unsaid in therapeutic relationships. Issue 1 (2nd January 2017) - Sen, Dolly
Abstract: This piece will explore my experiences accessing psychological therapies, concentrating on two different psychodynamic therapies and therapists I have had. One was more productive than the other. I will talk about what worked for me, what didn't work; equality & identity on the "wrong" side of the therapeutic relationship; what happens to shame when one person is protected from it and the other isn't; and finally what happens if your therapist doesn't share your ethnicity or sexuality, how can you talk about things like racism and homophobia when they don't "get" where your pain is coming from. I will finish the piece on what was the best experience of therapy I have ever had and why.